Unhealthy weight control behaviors, disordered eating, and body image dissatisfaction in adolescents from São Paulo, Brazil - Leal,Greisse V. da S. (2020)
Objective: To identify the frequency of disordered eating (DE) and unhealthy weight control behaviors (UWCB) among adolescents and associations with age, sex, actual weight status, perceived weight status, and body image dissatisfaction. Methods: Cross-sectional study of 1,156 adolescents. DE was assessed using a specific self-report questionnaire, UWCB by specific behaviors that were not typically recommended for weight management, and body dissatisfaction by Stunkard’s silhouettes. Results: The frequency of DE was 17.3%, and that of UWCB, 31.9%; 80.1% of participants were dissatisfied with body image. Perception of oneself as overweight was associated with 1.795-fold odds of DE. Those with UWCB had 7.389-fold odds of DE, while DE increased the odds of UWCB 7.280-fold. Girls, participants who perceived themselves as overweight, and those who reported body dissatisfaction were 2.266, 2.381, and 1.752 times more likely to have UWCB, respectively. Conclusion: A high prevalence of UWCB and a moderate prevalence of DE behaviors was found in adolescents from the city of São Paulo, Brazil. Those who perceived themselves as overweight had more DE and UWCB, and both behaviors were related. UWCB was more common in girls and among those dissatisfied with their bodies.